Breast milk DHA levels may increase after informing women: a community-based cohort study from South Dakota USA. Issue 1 (December 2016) - Juber, Brian; Jackson, Kristina; Johnson, Kristopher; Harris, William; Baack, Michelle
Abstract Background Docosahexaenoic acid (DHA), an omega-3 fatty acid found in breast milk, has many health benefits for both mother and baby. A 2007 meta-analysis found U.S. women had breast milk DHA levels (0.20% of total fatty acids) below the worldwide mean (0.32%). In 2008, international dietary recommendations were made for pregnant and lactating women to consume 200 mg of DHA per day. This community-based study aimed to define current milk DHA levels from upper Midwest USA lactating mothers and to determine if providing information about their own level along with dietary recommendations would incite changes to increase breast milk DHA content. Methods New mothers attending lactation classes or using hospital pumping rooms in Sioux Falls, South Dakota, USA participated by providing one drop of breast milk on a card for fatty acid analysis at baseline and 1 month after initial reporting. DHA levels were analyzed by gas chromatography. Mothers received a report of their own breast milk level along with dietary recommendations on DHA intake for lactating women. Median baseline and follow-up DHA levels were determined and differences were compared by Wilcoxon signed-rank test. Results At baseline, breast milk DHA content (n = 84) was highly variable (range 0.05 to 0.73%) with a median of 0.18% (IQR, 0.13, 0.28; mean ± SD, 0.22 ± 0.13%), well below the worldwide average (0.32%). Women who reported taking DHA supplements (n = 43) had higher levels than those who did not (0.23% vs. 0.15%, P < 0.0001). In a subset of 60 mothers who submitted a second sample, median breast milk DHA content increased from 0.19 to 0.22% (P < 0.01). Conclusions Findings suggest that providing nursing mothers with their breast milk DHA level and education about DHA intake while breastfeeding motivates change to increase DHA levels.